2020
DOI: 10.1002/adom.202001440
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Phase Segregation in Mixed Halide Perovskites: Thermodynamic and Kinetic Aspects of Cl–Br Segregation

Abstract: Suppression of halide ion mobility remains a key issue in defining the device performances and stability of perovskite solar cells. The halide ion migration is facilitated by the lattice‐distortion‐mediated halide vacancy and hence dictated by the polarizability (or rigidity) of the halide sublattice and framework. Photoinduced halide ion segregation and dark recovery of MAPb(Cl0.5Br0.5)3 films are now probed. The temperature dependence of the rate constants of segregation and dark remixing allow to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 64 publications
4
77
1
Order By: Relevance
“…[41,45] The halide vacancies, which promote mobility of halide ions, can thus influence the segregation rate and efficiency of phase segregation. [46] Photoexcitation of 3D mixed halide perovskite films leads to complete charge separation. [27,47] The long-lived charge carriers are beneficial for photocurrent generation in solar cells.…”
Section: Thermodynamics Of Phase Segregationmentioning
confidence: 99%
“…[41,45] The halide vacancies, which promote mobility of halide ions, can thus influence the segregation rate and efficiency of phase segregation. [46] Photoexcitation of 3D mixed halide perovskite films leads to complete charge separation. [27,47] The long-lived charge carriers are beneficial for photocurrent generation in solar cells.…”
Section: Thermodynamics Of Phase Segregationmentioning
confidence: 99%
“…Unfortunately, the halide composition of MAPb­(I 1– x Br x ) 3 ( x = 0.3) results in segregation into I- and Br-rich domains under illumination. The effective bandgap reduction leads to open-circuit voltage ( V oc ) losses, which in turn reduces the PCE in the corresponding PSCs . Several mechanistic models have been adopted to describe the phase segregation mechanism, which includes polaron-induced lattice strain, the existence of a two-state model, , and halide vacancy formation. , However, the complex interplay between thermodynamics and kinetics in the movement of halide ions makes the system interesting, and a detailed understanding of thermally activated halide segregation is challenging and at the same time important. Reportedly, the rate of segregation increases with temperature and a minimum excitation intensity is necessary to overcome the thermodynamic barrier of entropy of the mixing of halides. It is thus suggested that the thermally activated process dictates the demixing of the halides.…”
mentioning
confidence: 99%
“…The phase segregation induced spectrum instability has been frequently reported in alloyed CsPbCl x Br 3− x NCs, [ 59,60 ] which should be addressed before the sensing applications. As shown in Figure a; Figure S9, Supporting Information, the PL of CsPbCl 1.2 Br 1.8 NCs@ h ‐SiO 2 @EVA film retains at 99.7% of the initial intensity after the heating/cooling cyclings from 25 °C to 60 °C, showing the high thermal stability of CsPbCl 1.2 Br 1.8 NCs@ h ‐SiO 2 @EVA film.…”
Section: Resultsmentioning
confidence: 99%